Logic Restructuring with Preserved Logic Blocks - Lee, Siang-Yun; Riener, Heinz; Richter, Sascha; Sood, Ankush (2025 62nd ACM/IEEE Design Automation Conference (DAC), 2025)
During technology mapping, complex cells such as adders and multiplexers are often available in the standard cell library, which helps improve the final PPA results. However, technology-independent optimization tends to over-optimize towards the cost metrics measurable with technology-independent representations (e.g., AIG size) by decomposing blocks of logic that could have been mapped into complex cells. Besides, it is also of practical interest to model and preserve some special logic components, such as the enable logic of flops, during optimization. This paper studies "boxing" logic blocks before technology-independent optimization and preserving them during optimization. A wire-based resubstitution is proposed to optimize boxed networks. Experiments with academic and industrial benchmarks show that transparent-boxing, i.e., preserving boxes while utilizing the information on their logic, achieves better results than black-boxing, i.e., completely ignoring the logic in boxes. Specifically, in the technology-independent evaluation, transparentboxing reduces the mapped network size by 4% more than blackboxing; in the full-flow evaluation, transparent-boxing achieves 1.8% more improvement on timing and similar improvements in area, power, and wire length compared to black-boxing.